Thymus of Buffalo: Ultra Structural Perspective - Parkash, Tej; Poonia, Amit; Gahlot, Parveen Kumar (Indian Journal of Veterinary Anatomy, 2026)
Ultrastructural features of the thymus were studied in five young buffalo with age ranges from 1 to 1.5years old. In the cortex, densely packed thymocytes (lymphocytes) in various stages of differentiation wereobserved. The shapes of thymocytes were round to elliptic in outline. The cytoplasm was poor in terms oforganelles. Thymic epithelial cells (TEC) were also observed throughout the cortex. They were characterised bypale, electron-lucent cytoplasm, irregular shape with long cytoplasmic processes connected to each other bydesmosomes to form a reticular network. In medulla, a loose arrangement of mature thymocytes, and medullarythymic epithelial cells (TECs) were observed. There was degenerative nuclear and cytoplasmic structure in thecentral part of Hassall's corpuscles. Additionally, other cell types within the thymus, including macrophages andmast cells, which contribute to the phagocytic clearance of apoptotic thymocytes and antigen presentation werealso observed.